Dietary flavonoids among children and adolescents in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study: intake, food sources and trends from 1985 until 2016 - Rienks, Johanna; Penczynski, Katharina J.; Schmitting, Sarah; Buyken, Anette; Nöthlings, Ute (British Journal of Nutrition)
Abstract Flavonoids are suggested to reduce disease risk. Since dietary habits are acquired during early life, describing age and time trends of flavonoid intake and major food sources are important for monitoring and disease prevention in later life. We aimed to describe total flavonoid intake and food sources and to investigate age and time trends of flavonoid intake in 3–18-year-olds, from the Dortmund Nutritional and Anthropometric Longitudinally Designed study from 1985 to 2016. Intake was assessed annually using 3-d weighed food records (WFR). Flavonoid values were assigned using the United States Department of Agriculture database. Foods contributing to intake were determined. Age and time trends in total flavonoid and isoflavone density were analysed by sex with PROC MIXED. In total, 1312 children completed 10 758 WFR. Across all ages, daily mean total flavonoid density was lower in boys compared with girls (134 v . 146 mg/4184 kJ) and no difference in median isoflavone density (0·04 mg/4184 kJ per d) was found. The top five foods contributing to total flavonoid intake were apple with peel (15·0/17·1 %), strawberries (5·9/6·1 %), chocolate spread (3·9/3·5 %), orange juice (3·5/3·4 %) and pasta (3·5/3·4 %) for boys and girls, respectively. Overall, in boys, total flavonoid density decreased over the course of age and time. In girls, there was no association with age or time. In both sexes, isoflavone density followed a U-shaped age trend with no change over time. From a public health perspective, the overall observed downwards trend of flavonoid intake in boys deserves attention. Future initiatives should be tailored at maintaining a high flavonoid density as children age, specifically among boys.

Short-term metreleptin treatment of patients with anorexia nervosa: rapid on-set of beneficial cognitive, emotional, and behavioral effects - Milos, Gabriella; Antel, Jochen; Kaufmann, Lisa-Katrin; Barth, Nikolaus; Koller, Antonia; Tan, Susanne; Wiesing, Urban; Hinney, Anke; Libuda, Lars; Wabitsch, Martin; von Känel, Roland; Hebebrand, Johannes (Translational Psychiatry)
Abstract To examine the hypothesis that normalization of low circulating leptin levels in patients with anorexia nervosa ameliorates hyperactivity, three seriously ill females with hyperactivity were treated off-label with metreleptin (recombinant human leptin) for up to 14 days. Drive for activity, repetitive thoughts of food, inner restlessness, and weight phobia decreased in two patients. Surprisingly, depression improved rapidly in all patients. No serious adverse events occurred. Due to obvious limitations of uncontrolled case series, placebo-controlled clinical trials are mandatory to confirm the observed rapid onset of beneficial effects. Our findings suggest an important role of hypoleptinemia in the mental and behavioral phenotype of anorexia nervosa.

The Role of Genetic Variation of BMI, Body Composition, and Fat Distribution for Mental Traits and Disorders: A Look-Up and Mendelian Randomization Study - Peters, Triinu; Nüllig, Lena; Antel, Jochen; Naaresh, Roaa; Laabs, Björn-Hergen; Tegeler, Lisa; Amhaouach, Chaima; Libuda, Lars; Hinney, Anke; Hebebrand, Johannes (Frontiers in Genetics)

Early changes in hepatic energy metabolism and lipid content in recent-onset type 1 and 2 diabetes mellitus - Kupriyanova, Yuliya; Zaharia, Oana Patricia; Bobrov, Pavel; Karusheva, Yanislava; Burkart, Volker; Szendroedi, Julia; Hwang, Jong-Hee; Roden, Michael; Roden, M.; Al-Hasani, H.; Burkart, V.; Buyken, Anette; et al. (Journal of Hepatology)

World trends in sugar-sweetened beverage and dietary sugar intakes in children and adolescents: a systematic review - Della Corte, Karen; Fife, Jessica; Gardner, Alexis; Murphy, Britta L; Kleis, Linda; Della Corte, Dennis; Schwingshackl, Lukas; LeCheminant, James D; Buyken, Anette (Nutrition Reviews)
Abstract Objective To provide a systematic overview of world dietary sugar and sugar-sweetened beverage (SSB) intake trends in children and adolescents. Data Sources Medline, Embase, and the Cochrane Central Register of Controlled Trials in the Cochrane Library were searched through January 2019 to identify longitudinal follow-up studies with time-trend data and repeated cross-sectional studies. Data Extraction Data from studies reporting ≥ 2 measurements (sugars, SSB, or sweets/candy) over ≥ 2 years and included ≥ 20 healthy, normal- or overweight children or adolescents aged 1–19 years. Data Analysis Data from 43 articles (n = 4 prospective cohort studies; n = 39 repeated cross-sectional studies) from 15 countries (n = 8 European countries plus Australia, Canada, China, South Korea, Mexico, Russia, and the United States) are presented narratively. According to the risk of bias in nonrandomized studies of interventions tool, 34 studies were judged to have a moderate risk of bias, and 5 to have a serious risk of bias. Conclusions Consumption among US children and adolescents increased substantially in the decades preceding 2000, followed by a faster and continued decline. As a whole, other international intake trends did not reveal drastic increases and decreases in SSB and dietary sugars; they tended to change only slightly across 3 decades.

Dietary Fibre Consensus from the International Carbohydrate Quality Consortium (ICQC) - Augustin, Livia S. A.; Aas, Anne-Marie; Astrup, Arnie; Atkinson, Fiona S.; Baer-Sinnott, Sara; Barclay, Alan W.; Brand-Miller, Jennie C.; Brighenti, Furio; Bullo, Monica; Buyken, Anette; Ceriello, Antonio; Ellis, Peter R.; et al. (Nutrients)
Dietary fibre is a generic term describing non-absorbed plant carbohydrates and small amounts of associated non-carbohydrate components. The main contributors of fibre to the diet are the cell walls of plant tissues, which are supramolecular polymer networks containing variable proportions of cellulose, hemicelluloses, pectic substances, and non-carbohydrate components, such as lignin. Other contributors of fibre are the intracellular storage oligosaccharides, such as fructans. A distinction needs to be made between intrinsic sources of dietary fibre and purified forms of fibre, given that the three-dimensional matrix of the plant cell wall confers benefits beyond fibre isolates. Movement through the digestive tract modifies the cell wall structure and may affect the interactions with the colonic microbes (e.g., small intestinally non-absorbed carbohydrates are broken down by bacteria to short-chain fatty acids, absorbed by colonocytes). These aspects, combined with the fibre associated components (e.g., micronutrients, polyphenols, phytosterols, and phytoestrogens), may contribute to the health outcomes seen with the consumption of dietary fibre. Therefore, where possible, processing should minimise the degradation of the plant cell wall structures to preserve some of its benefits. Food labelling should include dietary fibre values and distinguish between intrinsic and added fibre. Labelling may also help achieve the recommended intake of 14 g/1000 kcal/day.

Inflammatory mediators in the adipo-renal axis: leptin, adiponectin, and soluble ICAM-1 - Hua, Yifan; Herder, Christian; Kalhoff, Hermann; Buyken, Anette; Esche, Jonas; Krupp, Danika; Wudy, Stefan A.; Remer, Thomas (American Journal of Physiology-Renal Physiology)
A lower 24-h urine pH (24h-pH), i.e., a higher renal excretion of free protons, at a given acid load to the body, denotes a reduction in the kidney’s capacity for net acid excretion (NAE). There is increasing evidence, not only for patients with type 2 diabetes but also for healthy individuals, that higher body fatness or waist circumference (WC) has a negative impact on renal function to excrete acids (NAE). We hypothesized that adiposity-related inflammation molecules might mediate this relation between adiposity and renal acid excretion function. Twelve biomarkers of inflammation were measured in fasting blood samples from 162 adult participants (18–25 yr old) of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had undergone anthropometric measurements and collected 24-h urine samples. Both Baron and Kenny’s (B&K’s) steps to test mediation and causal mediation analysis were conducted to examine the potential mediatory roles of biomarkers of inflammation in the WC-24-h pH relationship after strictly controlling for laboratory-measured NAE. In B&K’s mediation analysis, leptin, soluble intercellular adhesion molecule 1 (sICAM-1), and adiponectin significantly associated with the outcome 24-h pH and attenuated the WC-pH relation. In agreement herewith, causal mediation analysis estimated the “natural indirect effects” of WC on 24-h pH via leptin ( P = 0.01) and adiponectin ( P = 0.03) to be significant, with a trend for sICAM-1 ( P = 0.09). The calculated proportions mediated by leptin, adiponectin, and sICAM-1 were 64%, 23%, and 12%, respectively. Both mediation analyses identified an inflammatory cytokine (leptin) and an anti-inflammatory cytokine (adiponectin) along with sICAM-1 as being potentially involved in mediating adiposity-related influences on renal acid excretion capacity.

Early life factors and their relevance to intima-media thickness of the common carotid artery in early adulthood - Nyasordzi, Juliana; Penczynski, Katharina; Remer, Thomas; Buyken, Anette (PLOS ONE)

Reply to Khan et al. - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)

Sugar intake among German adolescents: trends from 1990 to 2016 based on biomarker excretion in 24-h urine samples - Perrar, Ines; Gray, Nicola; Kuhnle, Gunter G.; Remer, Thomas; Buyken, Anette; Alexy, Ute (British Journal of Nutrition)
Abstract Trend analyses based on dietary records suggest decreases in the intakes of total sugar (TS), added and free sugar since 2005 among children and adolescents in Germany. In terms of age trends, TS intake decreased with increasing age. However, self-reported sugar intake in epidemiological studies is criticised, as it may be prone to bias due to selective underreporting. Furthermore, adolescents are more susceptible to underreporting than children. We thus analysed time and age trends in urinary fructose excretion (FE), sucrose excretion (SE) and the sum of both (FE + SE) as biomarkers for sugar intake among 8·5–16·5-year-old adolescents. Urinary sugar excretion was measured by UPLC-MS/MS in 997 24-h urine samples collected from 239 boys and 253 girls participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study cohort between 1990 and 2016. Time and age trends of log-transformed FE, SE and FE + SE were analysed using polynomial mixed-effects regression models. Between 1990 and 2016, FE as well as FE + SE decreased (linear time trend: P = 0·0272 and P < 0·0001, respectively). A minor increase in excretion during adolescence was confined to FE (linear age trend: P = 0·0017). The present 24-h excretion measurements support a previously reported dietary record-based decline in sugar intake since 2005. However, the previously seen dietary record-based decrease in TS from childhood to late adolescence was not confirmed by our biomarker analysis, suggesting a constant sugar intake for the period of adolescence.

The Relationship between Glycemic Index and Health - Brand-Miller, Jennie; Buyken, Anette (Nutrients)
There is no question that elevated postprandial glycemia is a significant driver of common chronic diseases globally [...]

Effect of vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients: results of a randomized controlled trial - Libuda, Lars; Timmesfeld, Nina; Antel, Jochen; Hirtz, Raphael; Bauer, Jens; Führer, Dagmar; Zwanziger, Denise; Öztürk, Dana; Langenbach, Gina; Hahn, Denise; Ring, Stefanie; Peters, Triinu; et al. (European Journal of Nutrition)
Abstract Purpose While observational studies revealed inverse associations between serum vitamin D levels [25(OH)D] and depression, randomized controlled trials (RCT) in children and adolescents are lacking. This RCT examined the effect of an untreated vitamin D deficiency compared to an immediate vitamin D 3 supplementation on depression scores in children and adolescents during standard day and in-patient psychiatric treatment. Methods Patients with vitamin D deficiency [25(OH)D ≤ 30 nmol/l] and at least mild depression [Beck Depression Inventory II (BDI-II) > 13] ( n = 113) were 1:1 randomized into verum (VG; 2640 IU vitamin D 3 /d) or placebo group (PG) in a double-blind manner. During the intervention period of 28 days, both groups additionally received treatment as usual. BDI-II scores were assessed as primary outcome, DISYPS-II (Diagnostic System for Mental Disorders in Childhood and Adolescence, Self- and Parent Rating) and serum total 25(OH)D were secondary outcomes. Results At admission, 49.3% of the screened patients ( n = 280) had vitamin D deficiency. Although the intervention led to a higher increase of 25(OH)D levels in the VG than in the PG (treatment difference: + 14 ng/ml; 95% CI 4.86–23.77; p = 0.003), the change in BDI-II scores did not differ (+ 1.3; 95% CI − 2.22 to 4.81; p = 0.466). In contrast, DISYPS parental ratings revealed pronounced improvements of depressive symptoms in the VG (− 0.68; 95% CI − 1.23 to − 0.13; p = 0.016). Conclusion Whereas this study failed to show a vitamin D supplementation effect on self-rated depression in adolescent in- or daycare patients, parents reported less depressive symptoms in VG at the end of our study. Future trials should consider clinician-rated depressive symptoms as primary outcome. Trial registration “German Clinical Trials Register” ( https://www.drks.de ), registration number: DRKS00009758

Evaluation of Metabolic Profiles of Patients with Anorexia Nervosa at Inpatient Admission, Short- and Long-Term Weight Regain—Descriptive and Pattern Analysis - Föcker, Manuel; Cecil, Alexander; Prehn, Cornelia; Adamski, Jerzy; Albrecht, Muriel; Adams, Frederike; Hinney, Anke; Libuda, Lars; Bühlmeier, Judith; Hebebrand, Johannes; Peters, Triinu; Antel, Jochen (Metabolites)
Acute anorexia nervosa (AN) constitutes an extreme physiological state. We aimed to detect state related metabolic alterations during inpatient admission and upon short- and long-term weight regain. In addition, we tested the hypothesis that metabolite concentrations adapt to those of healthy controls (HC) after long-term weight regain. Thirty-five female adolescents with AN and 25 female HC were recruited. Based on a targeted approach 187 metabolite concentrations were detected at inpatient admission (T0), after short-term weight recovery (T1; half of target-weight) and close to target weight (T2). Pattern hunter and time course analysis were performed. The highest number of significant differences in metabolite concentrations (N = 32) were observed between HC and T1. According to the detected main pattern, metabolite concentrations at T2 became more similar to those of HC. The course of single metabolite concentrations (e.g., glutamic acid) revealed different metabolic subtypes within the study sample. Patients with AN after short-term weight regain are in a greater “metabolic imbalance” than at starvation. After long-term weight regain, patients reach a metabolite profile similar to HC. Our results might be confounded by different metabolic subtypes of patients with AN.

Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children’s cognitive function in a randomized crossover study - Jansen, Kathrin; Tempes, Jana; Drozdowska, Alina; Gutmann, Maike; Falkenstein, Michael; Buyken, Anette; Libuda, Lars; Rudolf, Henrik; Lücke, Thomas; Kersting, Mathilde (European Journal of Clinical Nutrition)

Kommunale Planung für Senior*innen bis 2025. Fortschreibung des Altenhilfeplans aus dem Jahr 2013

Psychische Auffälligkeiten bei Kindern und Jugendlichen, für die das Jugendamt in Anspruch genommen wurde - Wagenknecht, Inga; Meier-Gräwe, Uta (Praxis der Kinderpsychologie und Kinderpsychiatrie)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Gemeinsam Forschung gestalten. Handreichung zu partizipativer Forschung - Lutz, Katharina; Offergeld, Jana; Freymuth, Nina; Arp, Anna Liza

Age and time trends in sugar intake among children and adolescents: results from the DONALD study - Perrar, Ines; Schmitting, Sarah; Della Corte, Karen W.; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)

Is there a soft drink vs. alcohol seesaw? A cross-sectional analysis of dietary data in the Australian Health Survey 2011–12 - Wong, Tommy H. T.; Buyken, Anette; Brand-Miller, Jennie C.; Louie, Jimmy Chun Yu (European Journal of Nutrition)

Dietary sugars and cardiometabolic risk factors: a network meta-analysis on isocaloric substitution interventions - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)
ABSTRACT Background There is controversy on the relevance of dietary sugar intake for cardiometabolic health. Objective The aim of this network meta-analysis (NMA) was to assess how isocaloric substitutions of dietary sugar with other carbohydrates affect cardiometabolic risk factors, comparing different intervention studies. Methods We included randomized controlled trials (RCTs) investigating the isocaloric effect of substituting dietary sugars (fructose, glucose, sucrose) with other sugars or starch on cardiometabolic risk markers, including LDL cholesterol, triacylglycerol (TG), fasting glucose (FG), glycated hemoglobin (HbA1c), insulin resistance (HOMA-IR), uric acid, C-reactive protein (CRP), alanine transaminase (ALT), aspartate transaminase (AST), and liver fat content. To identify the most beneficial intervention for each outcome, random-effects NMA was conducted by calculating pooled mean differences (MDs) with 95% CIs, and by ranking the surface under the cumulative ranking curves (SUCRAs). The certainty of evidence was evaluated using the Confidence In Network Meta-Analysis tool. Results Thirty-eight RCTs, including 1383 participants, were identified. A reduction in LDL-cholesterol concentrations was shown for the exchange of sucrose with starch (MD: −0.23 mmol/L; 95% CI: −0.38, −0.07 mmol/L) or fructose with starch (MD: −0.22 mmol/L; 95% CI: −0.39, −0.05 mmol/L; SUCRAstarch: 98%). FG concentrations were also lower for the exchange of sucrose with starch (MD: −0.14 mmol/L; 95% CI: −0.29, 0.01 mmol/L; SUCRAstarch: 91%). Replacing fructose with an equivalent energy amount of glucose reduced HOMA-IR (MD: −0.36; 95% CI: −0.71, −0.02; SUCRAglucose: 74%) and uric acid (MD: −23.77 µmol/L; 95% CI: −44.21, −3.32 µmol/L; SUCRAglucose: 93%). The certainty of evidence was rated very low to moderate. No significant effects were observed for TG, HbA1c, CRP, ALT, and AST. Conclusions Our findings indicate that substitution of sucrose and fructose with starch yielded lower LDL cholesterol. Insulin resistance and uric acid concentrations were beneficially affected by replacement of fructose with glucose. Our findings are limited by the very low to moderate certainty of evidence. This review was registered at www.crd.york.ac.uk/prospero as CRD42018080297.